Sistem Pelaporan Panen Kelapa Sawit, Karet, Produksi CPO (Crude Palm Oil) dan Inti Sawit di PTP Nusantara V Berbasis Short Message Service (SMS) - Muhammad Aji Priyatna; Rafialdi R. Abrus (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2007)
To facilitate the management in controlling oil palm, rubber, CPO or palm kernel production, PTPN Vput into practice “Reporting System of Oil Palm and Rubber Harvesting and CPO and Palm Kernel ProductionBased on Short Message Service” established internally by IT Department and supported by Agronomy andProcessing Department. The system was built using relatively reasonable price equipment namely: hand phone,connector and 1 unit PC complete with supporting application developed by IT Department using Visual Basicprogramming language, PHP and MySQL database server. SMS server sends daily production dataautomatically to HP number of Directors, Head of Department/Bureau, General Manager, Manager and userthat already listed on database. The implementation of Production data reporting via SMS makes the productiondelivery and monitoring process faster, and it will support the management in decision making process.Keywords: oil palm, SMS, production and management